Simulation of Gap Flow of an Underwater Vehicle-Launch Tube - Yuan-qing LIU; Chen-xing ZHANG; Xiang-yan CHEN; Fan-yu WANG (水下无人系统学报)
When the tail of an undersea vehicle passes through the seal ring, complex characteristics—such as high speed and separation flow—arise during the connection process of the bottom of the launch tube and the seal cavity. Considering these characteristics and using the dynamic boundary unsteady value simulation, the flow field evolution and pressure fluctuation characteristics in the vehicle-tube gap were studied under different initial pressure ratios and vehicle speeds. The results show that the instantaneous speed of the high-temperature and high-pressure gas at the bottom of the tube can exceed the speed of sound when entering the gap cavity in the initial stage of the tail connection. The airflow is reflected after hitting the seal ring away from the bottom of the tube and produces violent flow oscillations and pressure fluctuations. Owing to the movement of the vehicle, the connection area increases and the impact peak amplitude gradually decreases. The amplitude of pressure fluctuation increases linearly with the initial pressure ratio. When the initial pressure ratio is 3.0, the relative peak and valley values of the pressure fluctuation can reach 1.4 times and 0.5 times of the initial pressure, respectively. When the speed of the vehicle increases, the leakage rate and peak pressure increase and the time of occurrence is advanced; meanwhile, the pressure fluctuation period remains unchanged under the above parameters.